Impact Welding of Materials - Galvão, Ivan; Loureiro, Altino; Mendes, Ricardo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Recent industrial criteria increasingly require the production of multi-material components. However, the manufacturing requirements of these components are not met by conventional welding techniques. Alternative solid-state technologies, such as impact-based processes, must be considered. The impact welding family is composed of several processes, such as explosion welding, magnetic pulse welding, vaporizing foil actuator welding, and laser impact welding. These processes present very different length scales, providing the impact welding family with a broad applicability range. A sample of the cutting-edge research that is being conducted on the multidisciplinary field of impact welding is presented in this book.